260 Edoxaban anticoagulation for gynecological cancer with venous thromboembolism. (13th November 2020) - Odajima, S; Seki, T; Saito, R; Kato, S; Suzuki, E; Saito, M; Yanagida, S; Yanaihara, N; Takano, H; Yamada, K; Okamoto, A
Abstract : Objective: Venous thromboembolism (VTE) is increasingly being treated with oral direct Xa inhibitors, including edoxaban. However, direct evidence supporting the use of edoxaban for thrombosis associated with gynecological cancer is limited. Thus, we compared edoxaban to warfarin with regard to their efficacy, safety and convenience in gynecological cancer patients with VTE. Method: We reviewed the medical records of 317 gynecological cancer patients who received edoxaban or warfarin treatment for VTE between January 2011 and December 2018. Result: The median follow-up period was 712 days (16–2868). Of the 317 patients, 180 and 137 were treated with edoxaban or warfarin, respectively. Details of cancer types were as follows: ovarian cancer 110 (62%), endometrial cancer 40 (22%), cervical cancer 22 (12%) and others 8 (4%) in edoxaban group and 81 (59%), 37 (27%), 16 (12%), 3 (2%) in warfarin group. There was no significant difference between two treatments groups in terms of BMI, VTE site, cancer type, histological subtype and stage. Recurrence of VTE occurred in 16 patients (8.9%) in edoxaban group and 18 (13.1%) in warfarin group (p=0.31). Adverse events that required discontinuation of anticoagulation occurred in 1 patient (0.6%) with edoxaban and 6 patients (4.4%) with warfarin (p=0.06), and no fatal events in either group. Initial heparin bridge was employed in 63 patients (37.7%) and 115 patients (92.0%) of edoxaban and warfarin group, respectively (p<0.01). Conclusion: Edoxaban is effective, safe and convenient for VTE patients with gynecological cancers.